'Preclinical' rheumatoid arthritis in patients with celiac disease: A cross-sectional study. Issue 2 (4th March 2019) - Fayyaz, Beenish; Gunawan, Ferry; Rehman, Hafiz J.
ABSTRACT: Objective : Preclinical or latent RA is characterized by the presence of autoantibodies in the absence of clinical symptoms. The objective of this study was to identify the prevalence of preclinical RA in patients with Celiac disease in order to determine whether or not such individuals should be screened for RA based on the high-risk. Method : A cross-sectional study was carried out on patients with celiac disease in a tertiary care center in Rawalpindi, Pakistan. After initial assessment, RA-autoantibody levels (Rheumatoid factor and anti-CCP) were checked. Descriptive analysis was performed on the data gathered. Results : Sixteen patients with known celiac disease were identified to have positive rheumatoid factor and/or anti-CCP levels with an overall prevalence rate of 35%. This trend was significant for celiac patients having history of inflammatory arthritis and active celiac disease. No statistical significance was seen in baseline characteristics for categories of patients with positive rheumatoid factor versus with positive anti-CCP antibodies. Conclusion : Patients with CD can be considered as a high-risk group based on the high prevalence rate of rheumatoid factor/anti-CCP positivity observed in this study and should be considered for further RA screening/preventive studies. Abbreviations : RA = Rheumatoid arthritis; CD = Celiac disease; anti-CCP = anti-citrullinated cyclic peptide) antibodies; RF = Rheumatoid factor; GFD = Gluten-free diet